2014
DOI: 10.1016/j.biopsycho.2014.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of the N1 auditory evoked potential for sounds generated by the upper and lower limbs

Abstract: Sensory attenuation is typically observed for self-generated compared to externally generated action effects. In the present study we investigated whether auditory sensory suppression is modulated as a function of sounds being generated by the upper or lower limbs. We report sensory attenuation, as reflected in a reduced auditory N1 component, which was comparable for sounds generated by the lower and the upper limbs. Increasing temporal delays between actions and sounds did not modulate suppression of the N1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 91 publications
5
29
0
Order By: Relevance
“…Like sensory stimulus-evoked N100 (Mangun and Hillyard 1991; van Elk et al 2014), TMS-evoked N100 distributed mainly at vertex and their amplitudes are sensitive to TMS intensity. However, its amplitude at vertex was not significantly changed within subject by stimulating different brain areas as long as the TMS intensity was the same.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Like sensory stimulus-evoked N100 (Mangun and Hillyard 1991; van Elk et al 2014), TMS-evoked N100 distributed mainly at vertex and their amplitudes are sensitive to TMS intensity. However, its amplitude at vertex was not significantly changed within subject by stimulating different brain areas as long as the TMS intensity was the same.…”
Section: Discussionmentioning
confidence: 99%
“…However, unlike those mentioned components, the N100 component, the negative deflection peak around 100 ms after the onset of stimulus, can be obtained from many if not all tasks in sensory domains. For example, N100 has been found in auditory (van Elk et al 2014), visual (Mangun and Hillyard 1991), olfactory (Pause et al 1996), pain (Greffrath et al 2007), balance (Quant et al 2005), respiration blocking (Chan and Davenport 2008) and somatosensory paradigms (Wang et al 2008). Although the N100 effect from each paradigm was usually regarded as specific to that paradigm, the commonality of N100 across them suggests global implications in additional to task-, anatomy- or modality-specific interpretations.…”
Section: Introductionmentioning
confidence: 99%
“…The attenuation of the P2 was also inspected in some recent studies, with many reporting significant attenuation (Knolle, Schröger, Baess, & Kotz, 2012;Horváth & Burgyán, 2013;Knolle, Schröger, & Kotz, 2013;Van Elk, Salomon, Kannape, & Blanke, 2014;Horváth 2014c), and some reporting no attenuation (Sowman, Kuusik, & Johnson, 2012;and Ford et al, 2014). N1, P2, and the T-complex are not the earliest waveforms that are attenuated in a contingent paradigm.…”
Section: Typical Findings In the Contingent Paradigmmentioning
confidence: 99%
“…One may speculate for example, that results suggesting multiple causes show a significant attenuation of one ERP, but not of the other. It is suggested, for example, that N1-and P2-attenuations may be differentially affected by the presence of cerebellar lesions (Knolle et al, 2012), or by the type of the effector (hand vs. foot movements, Van Elk et al, 2014). Because there is no reason to assume that a single manipulation would have the same magnitude of effect on two ERP components, a convincing dissociation would have to show effects of different signs, that is, the manipulation would result in higher amplitude for one of the ERPs, and lower amplitude for the other.…”
Section: Typical Findings In the Contingent Paradigmmentioning
confidence: 99%
“…EEG studies aimed to better understand these responses (van Elk, et al, 2014a, van Elk, et al, 2014b) reported reduced N1 auditory components when participants listened to heart beat-related sounds compared with externally generated sounds (van Elk, et al, 2014a), and when participants listened to sounds generated by their own limbs (van Elk, et al, 2014b). The robust and persistent effect that the brain automatically differentiates between the interoceptive and externally generated sounds suggests that a predictive mechanism could be at play, comparable to similar mechanisms mediating sensory suppression of self-generated actions (Blakemore, et al, 1998).…”
Section: Multisensory Integration In the Auditory Cortexmentioning
confidence: 99%